Closed loop voltage control of a solenoid using parallel finite element method. Issue 4 (4th July 2016) - Marcsa, Daniel; Kuczmann, Miklós
Abstract : Purpose: – The purpose of this paper is to present the importance of model accuracy in closed loop control by the help of parallel finite element model of a voltage-fed solenoid with iron core. Design/methodology/approach: – The axisymmetric formulation of the domain decomposition-based circuit-coupled finite element method (FEM) is embedded in a closed loop control system. The control parameters for the proportional-integral (PI) controller were estimated using the step response of the analytical, static and dynamic model of the solenoid. The controller measures the error of the output of the model after each time step and controls the applied voltage to reach the steady state as fast as possible. Findings: – The results of the closed loop system simulation show why the model accuracy is important in the stage of the controller design. The FEM offers higher accuracy that the analytic model attained with magnetic circuit theory, because the inductance and resistance variation already take into account in the numerical calculation. Furthermore, parallel FEM incorporating domain decomposition to reduce the increased computation time. Originality/value: – A closed loop control with PI controllers is applied for a voltage driven finite element model. The high computation time of the numerical model in the control loop is decreased by the finite element tearing and interconnecting method with direct and iterative solver.